Außerhalb der Religion kein Heil?: Für eine performative Religionstheologie im Stil der Gastfreundschaft - Rosenhauer, Sarah (Zeitschrift für Theologie und Philosophie, 2025)
The phenomenon of the steady increase in religious indifference presents theology with a new urgency to theologically reflect on the relationship between Christian truth-claims and non-religious concepts of life and self. Starting from an understanding of religion as performative, according to which the essence of religion lies not in a particular confession, but in the ever-new performative realization of a modality of existence (Bruno Latour), a style of inhabiting the world (Christoph Theobald), this article examines the specificity of a Christian understanding of truth in order to derive criteria for an inter- and transreligious dialogue. Central to this is the concept of hospitality: without the encounter with the other, there can be no understanding of one's "own."